DETERMINAN STRUKTUR MODAL DAN KONSEKUENSINYA TERHADAP RETURN SAHAM PERUSAHAAN MANUFAKTUR - Wijang Wijayanti, 08.05.51.0005; Taswan, Taswan (Students Journal of Economic and Management, 2012)
The main objective of the study is to examine the impact of these factors on capital structure of manufacture industry that listed at Indonesia Stock Exchanges over 2008-2010. The objective of this research is to test and analyze whether sales growth, assets structure, profitability, business risk, dividend to firm capital structure, and to analys the influence of capital structure to return stock. Thirty five companies met the criteria and were analyzed descriptive statistic and multiple regression were performed to test the hypothesis. Hypothesis testing is based on agency theory, signaling theory, asymmetric information theory, packing order theory, and previously empirical evidence. The conclusion show that assets structure, profitability are influence firm capital structure, but sales growth, business risk, dividend are not significant impact of firm capital structure. The other conclusion show that capital structure is not influece return assets.Key words : sales growth, assets structure, profitability, business risk, dividend, capital structure, return stock